ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN KERJA PADA SISWA KELAS XII SMK MANDIRI PONTIANAK - Alehatina yarso; F.Y. Khosmas; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the factors that affect job readiness in class XII accounting students at SMK Mandiri East Pontianak. This research is based because class XII students will graduate from school and enter the workforce, then students must first have work readiness in order to play their role well in the world of work. The research method used is descriptive method with a qualitative approach and forms of survey research. The source of data in this study were students of class XII accounting expertise program 1 and accounting 2. Data collection is obtained through interview guidelines then analyzed using data reduction, data presentation, and verification/conclusion drawing, then data validity uses time triangulation. Researchers conducted research and interview with accounting class XII students, amounting to 9 students as much 2 times. The results showed that the motivational factors, knowledge factors, talent factors, interest factors, and learning achievement factors of students who affected him had readiness to work after graduating school. Keywords: Factors Affecting Work readiness